On My Right Michael, on My Left Gabriel Angels in Ancient Jewish Culture - Ahuvia, Mika 1983- (Berkeley University of California Press, 2021)
Angelic beings can be found throughout the Hebrew Bible, and by late antiquity the archangels Michael and Gabriel were as familiar as the patriarchs and matriarchs, guardian angels were as present as one's shadow, and praise of the seraphim was as sacred as the Shema prayer. Mika Ahuvia recovers once-commonplace beliefs about the divine realm and demonstrates that angels were foundational to ancient Judaism. Ancient Jewish practice centered on humans' relationships with invisible beings who acted as intermediaries, role models, and guardians. Drawing on non-canonical sources--incantation bowls, amulets, mystical texts, and liturgical poetry--Ahuvia shows that when ancient men and women sought access to divine aid, they turned not only to their rabbis or to God alone but often also to the angels. On My Right Michael, On My Left Gabriel spotlights these overlooked stories, interactions, and rituals, offering a new entry point to the history of Judaism and the wider ancient Mediterranean and Near Eastern world in which it flourished.
Intro -- Imprint -- Subvention -- Title Page -- Copyright -- Dedication -- Contents -- Acknowledgments -- Introduction: Angelic Greetings or Shalom Aleichem -- 1. At Home with the Angels -- 2. Out and About with the Angels: Palestinian Ritual Sources -- 3. No Angels? Early Rabbinic Sources -- 4. In the Image of God, Not Angels: Rabbinic Sources -- 5. In the Image of the Angels: Liturgical Responses -- 6. Israel among the Angels: Late Rabbinic Sources -- 7. Jewish Mystics and the Angelic Realms: Early Mystical Sources -- Conclusion: Angels in Judaism and the Religions of Late Antiquity -- Appendix: Table of Incantation Bowls -- Notes -- Bibliography -- Index.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books